Comparison of BOR1-like gene expression in two genotypes with different boron efficiencies in commercial crop plants in Thailand - Sumana Leaungthitikanchana (2018)
In Thailand, boron (B) deficiency in soil is found in the north region where wheat (Triticum aestivum L.), maize (Zea mays L.) and rice (Oryza sativa L.) are promoted cereals. Physiological analysis and genetic variation in B efficiency among plant genotypes have been reported; however, the molecular and genetic mechanisms of low B tolerance remain unclear. In this present study, we investigated the molecular basis of low B tolerance in wheat, maize and rice. Transcript levels of BOR1-like genes, efflux-type B transporters, were compared between B-efficient and B-inefficient genotypes in different organs using quantitative real-time polymerase chain reaction (PCR). The results revealed that the transcript levels of BOR1-like genes are differential between two different genotypes. We found the tendency that transcripts of BOR1-like gene are accumulated to higher levels in B deficiency tolerant cultivar than the sensitive ones in most tested tissues. It is possible that the expression levels of BOR1-like genes are correlated with the B deficiency tolerance in plants. Moreover, BOR1-like genes can be useful as gene expression biomarkers for crop breeding in wheat, maize and rice by selecting appropriate tissues and growth stages. © 2014 Japanese Society of Soil Science and Plant Nutrition.